2017
DOI: 10.1016/j.jor.2017.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Review: Medial collateral ligament injuries

Abstract: The medial collateral ligament (MCL) is a major stabilizer of the knee joint. It is the most common ligament injured in the knee, particularly in athletes, and has been reported to be torn in 7.9% of all knee injuries. The MCL has a complex, layered anatomy with multiple insertions and functions. Minor trauma can cause tearing of the superficial portion whereas higher energy mechanisms can disrupt both the deep and superficial layers. History and physical are often adequate, but the gold standard for diagnosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
74
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(76 citation statements)
references
References 16 publications
0
74
0
2
Order By: Relevance
“…MCL injury treatment has been a topic of debate, with a general consensus to treat grade I and II injuries (Hughston classification system) conservatively. 8 , 15 This is because of the superior healing potential and vascularity of the MCL in comparison to the ACL. 16 Treatment of grade III MCL injuries remains a topic of controversy, especially with concomitant ACL injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MCL injury treatment has been a topic of debate, with a general consensus to treat grade I and II injuries (Hughston classification system) conservatively. 8 , 15 This is because of the superior healing potential and vascularity of the MCL in comparison to the ACL. 16 Treatment of grade III MCL injuries remains a topic of controversy, especially with concomitant ACL injury.…”
Section: Discussionmentioning
confidence: 99%
“… 6 , 7 The DMCL resists valgus stresses and is a secondary restraint alongside the medial meniscus to anterior tibial translation. 8 Cadaveric studies have shown that knees with an incompetent MCL exhibited increased loading patterns on the ACL. 9 , 10 …”
mentioning
confidence: 99%
“…The most common injuries are those of the medial collateral ligament (MCL) [ 1 , 2 , 3 ], produced by distortion of the knee with valgus deviation and external rotation. This injury is particularly frequent especially in professional athletes [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The authors describe the case of a 48-year-old man with a bilateral rupture of the patellar tendons, combined with a bilateral complete tear of the MCL. These lesions occur frequently in isolation [ 3 , 4 ], but the uniqueness of this case lies in the bilateral combination of both lesions. No reports of an exactly similar case have been found in the literature.…”
Section: Introductionmentioning
confidence: 99%